Will melatonin supplementation become a new form of obesity treatment? A review of recent literature. - Żak, Natalia; Błaszczyk, Aleksandra; Pażyra, Aldona; Kusak, Natalia; Jaworska, Barbara; Stanicki, Paweł (Quality in Sport, 2024)
Background: In 2020, the World Health Organization (WHO) estimated that 650 million adults worldwide are obese, and 2.8 billion individuals struggle with overweight. Obesity is associated with an increased risk of cardiovascular diseases, type 2 diabetes, heart disease, adverse effects on mental health, the development of certain cancers, and other conditions. In recent years, there has been growing interest in the role of melatonin, which has therapeutic potential in the treatment of obesity. Studies suggest that melatonin supplementation may lead to weight reduction and improvement in metabolic parameters, significantly reduce cardiovascular disease risk factors, and enhance insulin sensitivity in obese individuals. Aim of study: This review aims to present the latest scientific findings on the impact of melatonin supplementation on the development of obesity and its complications. We focus primarily on the mechanisms of melatonin's action in the context of obesity, particularly on potential pathways that have not yet been thoroughly explored. Our aim is to provide deeper insights into research on obesity and its prevention. Materials and Methods: Search was conducted using PubMed and Google Scholar databases, utilizing the keywords "obesity," "melatonin," and "weight loss" in various configurations. The review primarily considers studies published after 2016 that are available online. Summary Melatonin supplementation leads to a statistically significant reduction in blood glucose levels and an increase in cellular insulin sensitivity. Its promising properties in the treatment of obesity have been demonstrated through the reduction of oxidative stress, indicating a potential adjunct for weight loss. Based on the cited studies, the beneficial effects of melatonin supplementation on cardiovascular risk factors have been confirmed. Melatonin could be considered as an adjunctive therapy for obese individuals who do not respond to other treatment modalities.